Elements of Islamic Principle of Village Financial Management (VFM) in Indonesia - Setiawan, Achdiar Redy; Yusoff, Murni (‘Abqari Journal, 2024)
Law No. 6 of 2014 concerning Villages is a historic milestone for village governance in Indonesia. Villages are given great authority to carry out village development autonomously, accompanied by a mandate to implement Village Financial Management (VFM). However, the large amount of funds under management raises various problems, especially the rampant abuse of authority in running VFM. This study aims to identify Islamic elements of VFM in Indonesia. The data collection method mainly uses document research, particularly referring to the Quran, Hadits, and other relevant pieces of literature. Moreover, this research also conducts interviews with some experts who understand issues related to Islamic perspectives associated with VFM to guide the identification process. The analysis method used in this study is thematic data analysis. The study concludes seven elements for the implementation of VFM based on an Islamic perspective. The elements of Islamic Principles of VFM are based on Islamic values, namely a) trustworthiness; b) honesty; c) accountability; d) transparency; e) clear, fair & "healthy" regulations; f) substantive participation, and g) collectiveness-togetherness work.